Pemodelan Klaim Asuransi Kendaraan Bermotor dengan Regresi ZAIG - Yulia Resti; Noriszura Ismail; Saiful Hafizah Jaaman (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2010)
In motor insurance pricing based on risk of policyholder, modeling claim is the most important step.The modeling includes two main models there are model which relates to event of claims and modelthe cost of claims submitted to insurance companies. Most studies modeling the cost of claimsinvolving only the amount of claims which are positive, i.e. when an accident happens and then thepolicyholder filed a claim with the claims cost is greater than zero. In one period of insurance, there’repolicyholders who have not had an accident and there’re policyholders who had an accident but doesnot have claim, in this case is said to the claims cost is zero. This paper investigate theimplementation ZAIG (Zero Adjusted Inverse Gaussian) regression on the model of automobileinsurance claims that involve the cost of claims that zero and positive use data supported byInsurance Services Malaysia (ISM) Berhard. By regression ZAIG note that both the event and theaverage of claim cost significantly affected by the premium.